Efectividad del láser en el proceso de cicatrización de los tejidos orales posterior a un procedimiento quirúrgico. Revisión sistemática de la literatura 2015-2023 (2023)
Laser is an acronym that stands for amplification of a beam of light stimulated by emission radiation, which is generated by a decline in energy from an excited and emitted species.